ANALISIS LINGUISTIK DIGITAL DALAM KONTEN FACEBOOK PRO: POLA PENGGUNAAN BAHASA IBU MUDA DI DUSUN GARANTIGA DAN HUBUNGANNYA DENGAN ENGAGEMENT AUDIENS - Amir, Johar; Dalle, Ambo; Sumarni, Sumarni (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to analyze the linguistic patterns used by young mothers in Dusun Garantiga, Maros Regency, on Facebook Pro content, and to examine the relationship between digital writing and speaking skills and audience engagement levels. The research employs a descriptive quantitative approach with digital linguistic analysis. Data were collected through digital observation and online documentation of 120 posts from ten selected Facebook Pro accounts using purposive sampling. The data were analyzed using descriptive statistics and Pearson and Spearman correlation tests with SPSS 25 for Windows. The results show that the linguistic patterns of young mothers’ digital communication are dominated by code-mixing (35%), informal style (28%), and netspeak (18%), indicating the use of casual greetings, abbreviations, emojis, and hashtags to create social closeness with audiences. Correlation analysis revealed a significant positive relationship between digital writing and speaking skills and engagement levels (r = 0.642; p < 0.05). Communicative and expressive language use was found to increase audience interactions such as likes, comments, and shares. Theoretically, this research enriches digital linguistics studies by highlighting community-based communication practices that have received limited academic attention. Practically, the findings offer recommendations for developing community-based digital communication literacy, particularly empowering young mothers in rural areas to utilize social media effectively as a medium for social and economic empowerment